Kepemilikan dan Pengendalian Investor Asing pada Perjanjian Hutang yang Dapat Dikonversi (Convertible Loan Agreement) sebagai Instrumen Investasi Luar Negeri - Diandra, Shamira (Universitas Ekasakti, 2023)
Overseas investment is one way for countries and companies in the country to obtain investment. The concept is given a forum in the Investment Law which provides regulations related to foreign investment in Indonesia, one of which is a derivative form of share acquisition, namely through the mechanism of converting debt into shares in a Convertible Loan Agreement. The research aims to analyse the arrangements related to the legality and concept of Convertible Loan Agreement and how the position of foreign investors in ownership and control through Convertible Loan Agreement. The juridical-normative research method with descriptive research type is used in this research. The research will be processed qualitatively based on literature study with data collection tools in the form of secondary data. Convertible Loan Agreement is one of the foreign investment instruments currently used by foreign investors. However, its provisions refer to the Civil Code and the Company Law. There are no derivative provisions from the Investment Law that define and regulate specifically related to the Convertible Loan Agreement. Convertible Loan Agreement is one of the instruments that can fulfil the element of